1998
DOI: 10.1159/000022009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Age on Oxidative Bursts (Chemiluminescence) of Polymorphonuclear Neutrophil Leukocytes

Abstract: The release of reactive oxygen species (ROS) during neutrophil oxidative bursts is the last of a sequence of different steps leading to the neutralization of pathogen microorganisms. Using luminol-amplified chemiluminescence (LACL), the oxidative burst activity of neutrophils in elderly people (≥75 years) was compared with that in younger controls (39 years on average) after activation with both particulate (Candida albicans) and soluble (formyl-methionyl-leucyl-phenylalanine; fMLP) stimulants. After Candida s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…The robust increase in Th1 cytokine response on account of probiotic supplementation was further assessed in conjunction with analysis of other immunological parameters. Many studies have reported various age-associated discrepancies in neutrophil functions including impaired respiratory burst and phagocytosis (Braga et al 1998;Tortorella et al 2000;Lord et al 2001). IFN-γ has been shown to enhance various neutrophil functions (Ellis and Beaman 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The robust increase in Th1 cytokine response on account of probiotic supplementation was further assessed in conjunction with analysis of other immunological parameters. Many studies have reported various age-associated discrepancies in neutrophil functions including impaired respiratory burst and phagocytosis (Braga et al 1998;Tortorella et al 2000;Lord et al 2001). IFN-γ has been shown to enhance various neutrophil functions (Ellis and Beaman 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It can be speculated that a changed nociception and pain behaviour during older age is responsible for these findings [9]. Biological studies showed that oxidative burst formation is impaired in the aged [4]. Eventually, the significantly better results in patients older than 58 years remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported normal superoxide production by neutrophils in response to FMLP, 19,31 whilst others have shown reduced responses 35,36 . Activation of PLD by FMLP receptor ligation leads to production of phosphatidic acid, which is able to activate NADPH oxidase.…”
Section: Age and Neutrophil Productionmentioning
confidence: 99%
“…26 Several authors have reported normal superoxide production by neutrophils in response to FMLP, 19,31 whilst others have shown reduced responses. 35,36 Activation of PLD by FMLP receptor ligation leads to production of phosphatidic acid, which is able to activate NADPH oxidase. 37 As FMLPinduced activation of PLD is not affected by age, 29,30 this supports those studies reporting a normal neutrophil superoxide response in the elderly.…”
Section: Microbicidal Mechanismsmentioning
confidence: 99%